The Influence of Liquidity and Solvency on Profitability at PT Indofood Makmur Sejahtera, Tbk - Dahlan Palenteng (PT FORMOSA CENDEKIA GLOBAL, 2022)
The aim of this research is to determine the effect of liquidity and solvency ratios on profitability at PT Indofood Makmur Sejahtera that produce food and beverage.listed on the IDX. Liquidity (X1) is proxied by current rasio, quick ratio, and cash ratio; Solvency (X2) is proxied by debt to asset ratio, debt to equity ratio. Profitability (Y) is proxied by return on asset ratio, and return on equity ratio. This research took time series data from financial statement in period 2015 to 2021. Data get analyzed by using classical assumption test, simple and multiple linear regression, and hypothesis testing using T test and F test. The results of this research showed that liquidity partially had a negative effect and had no significant effect on profitability. Solvency partially has a positive effect and had significant effect on profitability. Liquidity and solvency simultaneously had no effect on profitability